Scavenger receptor gp340 aggregates group A streptococci by binding pili - Edwards,AM; Manetti,AG; Falugi,F; Zingaretti,C; Capo,S; Buccato,S; Bensi,G; Telford,JL; Margarit,I; Grandi,G (Mol.Microbiol., 2008)
Group A streptococci (GAS) are the most frequent cause of bacterial pharyngitis. The first obstacle to GAS colonization of the pharynx is saliva. As well as forming a physical barrier, saliva contains components of innate and acquired immunity. Previous work has shown that saliva induces bacterial aggregation, which may serve as a clearance mechanism. As the aggregation of some oral streptococci in saliva is mediated by long proteinaceous appendages, we hypothesized that pili of GAS might behave similarly. Wild-type GAS M1 strain SF370 aggregated in saliva, while pilus-defective mutants did not. Similarly, heterologous expression of diverse GAS pili on the surface of Lactococcus lactis induced aggregation in saliva, while control strains were unaffected. Further studies revealed that aggregating bacteria bound salivary component gp340. Purified gp340 aggregated wild-type GAS and L. lactis expressing GAS pili, but not control strains. GAS pilus-defective mutants were abrogated in gp340 binding and aggregation. Furthermore, gp340-mediated aggregation reduced bacterial adhesion to human epithelial cells, suggesting a role in host defence